2017
DOI: 10.1111/jnc.14231
|View full text |Cite
|
Sign up to set email alerts
|

Impaired AMPA receptor trafficking by a double knockout of zebrafish olfactomedin1a/b

Abstract: The olfm1a and olfm1b genes in zebrafish encode conserved secreted glycoproteins. These genes are preferentially expressed in the brain and retina starting from 16 h post-fertilization until adulthood. Functions of the Olfm1 gene is still unclear. Here, we produced and analyzed a null zebrafish mutant of both olfm1a and olfm1b genes (olfm1 null). olfm1 null fish were born at a normal Mendelian ratio and showed normal body shape and fertility as well as no visible defects from larval stages to adult. Olfm1 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…This suggests that additional auxiliary subunits are involved in regulating the lateral mobility of synaptic GluA2-containing AMPARs [ 395 ]. In zebrafish double knockout for olfactomedin1 a/b, the homologs of Noelin-1, levels of synaptic AMPARs are significantly reduced; as GluA2 palmitoylation is decreased (but phosphorylation unaffected), this suggests that Noelin-1 regulates GluA2 maturation and thereby trafficking from the ER to the dendritic compartment, a role not mutually exclusive with regulating AMPAR lateral mobility [ 393 ] (Fig. 7 ).…”
Section: Noelinmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that additional auxiliary subunits are involved in regulating the lateral mobility of synaptic GluA2-containing AMPARs [ 395 ]. In zebrafish double knockout for olfactomedin1 a/b, the homologs of Noelin-1, levels of synaptic AMPARs are significantly reduced; as GluA2 palmitoylation is decreased (but phosphorylation unaffected), this suggests that Noelin-1 regulates GluA2 maturation and thereby trafficking from the ER to the dendritic compartment, a role not mutually exclusive with regulating AMPAR lateral mobility [ 393 ] (Fig. 7 ).…”
Section: Noelinmentioning
confidence: 99%
“…Another hypothesis would be that Noelin-1 enhances AMPAR surface stabilization, as it is present in lipid rafts, which have been shown to be important for this process [ 38 ]; however, the fact that AMPAR endocytosis is reduced in the mutant makes this possibility unlikely. Intriguingly, Noelin-1 is also present in the presynapse and interacts with SNARE proteins, which are also reduced in the presynaptic compartment in knockout fish [ 393 ]. Noelin-2 knockout mice show impaired behaviors and olfaction similar to Noelin-1 knockout mice, with additional slight motor defects; the composition of synaptic AMPAR complexes was also altered, with increased levels of GluA2, but decreased Noelin-1, PSD95, and CNIH-2 [ 394 ].…”
Section: Noelinmentioning
confidence: 99%
“…These new constructs, together with our previously published tetrameric Olfm1 BMZ construct, could also be used for in vitro cell or bead clustering assays to test if pre/post-synaptic receptor binding in trans is supported by Olfm1. Moreover, the Olfm1 BMY and Olfm1 coil-Olf constructs could be used as acute dominant negatives by interfering with one interaction but not linking to a third protein in functional assays, such as electrophysiological determination of synaptic input/output ratio or long-term potentiation, or morphological characterisation of synapses and dendritic spines, for example in combination with knockout or knockdown animals [22]. In conclusion, there are many exciting hypotheses about the functions of Olfm1 in the mature (mammalian) brain that remain to be tested, for which our novel constructs and their associated purification strategies might provide a starting point.…”
Section: Discussionmentioning
confidence: 99%
“…Olfm1 has been reported to interact with various nervous system cell surface receptors such as Amyloid Precursor Protein (APP) [13], the Nogo Receptor [14], and glutamate-gated ion channels of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor family GluA1–4 [8, 1524]. In recent years it was found that Olfm1 is enriched in synapses [8, 22] and proximity labelling identified its presence in the synaptic cleft [25, 26]. Taken together the findings that Olfm1 is secreted [4, 9, 10], interacts with synaptic cell surface receptors, is enriched in the synapse and is present in the synaptic cleft suggest that Olfm1 plays a role in this intercellular substructure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation